Do Cardiac Rehabilitation Affect Clinical Prognoses Such as Recurrence, Readmission, Revascularization, and Mortality After AMI?: Systematic Review and Meta-Analysis - Kim, Chul (Ann Rehabil Med, 2021)
OBJECTIVE: We conducted a systematic review and meta-analysis to analyze the effects of cardiac rehabilitation (CR) on post-discharge prognoses of patients with acute myocardial infarction (AMI). METHODS: A literature search was conducted through four international medical and two Korean databases. Primary outcomes for the effectiveness of CR included all-cause mortality, cardiovascular mortality, recurrence, revascularization, major adverse cardiovascular event, major adverse cardiocerebrovascular event, and readmission. We summarized and analyzed results of studies about CR for AMI, including not only randomized controlled trials (RCTs) but also non-RCTs. We calculated the effect size separately by the study type. RESULTS: Fourteen articles were finally selected. Of these, two articles were RCTs, while 12 were non-RCTs. In RCTs, the overall mortality rate was lower in the group that participated in CR than that in the conventional care group by 28% (relative risk=0.72; 95% confidence interval, 0.34–1.57). Among non-RCTs, CR participation significantly decreased the overall risk of mortality. Moreover, the rates of recurrence and major adverse cardiovascular events were lower in the group that participated in CR compared to those in the non-CR group. CONCLUSION: The meta-analysis shows that CR reduces the risk of re-hospitalization and all-cause mortality after AMI, compared to no participation in CR. This outcome was seen in RCTs as well as in non-RCTs. More studies are necessary for concrete conclusions about the beneficial effects of CR after AMI in various settings.